Developing and Playing Geometric Puzzle Game to Enhance the Ability of Mathematical Creative Thinking - Susiaty, Utin Desy; Prihatin, Iwit; Hartono, Hartono (Kreano, Jurnal Matematika Kreatif-Inovatif, 2021)
This study explores the development of the game media of the geometric puzzle to support junior high school students' mathematical creative thinking skills. The research design used in this RD research uses a 4-D development model. The researchers present the prototype of an exciting game for stimulating students’ creative thinking ability. Expert validation obtained an average value of 80.89%, the category is feasible (not revised). Students' limited trial score was 88.69% very interesting category and from the teacher 80% interesting category. The value of field trials to assess effectiveness through completeness obtained by students of 75.86% was categorized as complete classically. Therefore, the development of geometry puzzle game media with students' needs is feasible, interesting, and useful.Penelitian ini mengeksplorasi pengembangan media permainan puzzle geometris untuk mendukung kemampuan berpikir kreatif matematis siswa SMP. Desain penelitian yang digunakan dalam penelitian RD ini menggunakan model pengembangan 4-D. Para peneliti mempresentasikan prototipe permainan yang menarik untuk merangsang kemampuan berpikir kreatif siswa. Validasi ahli memperoleh nilai rata-rata 80,89% kategori layak (tidak direvisi). Nilai uji coba terbatas siswa 88,69% kategori sangat menarik dan dari guru 80% ka-tegori menarik. Nilai uji coba lapangan untuk menilai keefektifan melalui ketuntasan yang diperoleh siswa sebesar 75,86% dikategorikan tuntas secara klasikal. Oleh karena itu, pengembangan media permainan puzzle geometri yang sesuai dengan kebutuhan siswa layak, menarik, dan bermanfaat.